Regic: Trajetória, variaç\~oes e hierarquia urbana em 2018 - Rosa Moura; Liria Nagamine; Gustavo Ferreira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– In this text for discussion, a synthesis of the trajectory of the line of research on the Regions of Influence of Brazilian Cities, developed by IBGE, whose content excels in the longevity, systematcity and timeliness of complex research that expresses the Brazilian urban network since the 1960s, is elaborated. In addition to history of this trajectory, some results and advances of the most recent research, available in 2018, are highlighted in the text. It highlights the importance of studies on urban hierarchy and regions of influence of cities, and general considerations are made about the historical and methodological aspects of research, with emphasis on quality and ease of access to the information produced. In the historical construction, it approaches that the improvement of operational procedures did not compromise methodological comparability and results, which ensured to follow the evolution, over time, of the positioning of each city on the scale of the urban network. Returning to the structuring of the urban network, the text presents the results of an exercise that sought to demarcate the changes and permanence of cities in the hierarchical scale throughout the analyzed period. There were also important changes in the variation of centrality levels, related to the rise or fall in rescheduling over the period. The international connections of the cities of the land border strip and the long-distance international connections of all cities also deserved to be highlighted in the text that is presented, for the novelty in the series of researches considered. Finally, the importance of the research and the firmness of IBGE in the production of a series of high quality and constant periodicity is renewed. It is emphasized how much its results point to the urgency of a reflection on the federative pact, since the socio-spatial dynamics increasingly ignore snow and borders.
Keywords: R11; R23; R58; 330; Regic; urban hierarchy; urban network; regions of influence of cities